Correlation between the Systemic Immunoinflammatory Index and Platelet–Lymphocyte Ratio in Patients with Adenomyosis - Yan Dong; YaHui Chen; YaNan Wang; Lin Wang; Yan Zhou; Mei Xue; Lin Sun (Mediators of Inflammation)
Background. The chronic inflammatory immune response is a significant factor in the pathogenesis of benign gynecological diseases. The systemic immunoinflammatory index (SII) and the platelet-to-lymphocyte ratio (PLR) are commonly available biomarkers of inflammation. However, evidence of the relationship between SII and PLR in patients with adenomyosis is limited. This study aimed to investigate the relationship between SII and PLR in patients with adenomyosis. Methods. This cross-sectional study included 483 patients with adenomyosis who were first diagnosed at our institution between January 2019 and December 2021. Basic patient clinical information and inflammatory factors were collected for univariate analysis, smoothed curve fitting, and multivariate segmented linear regression. Results. The results of the univariate analysis showed a significant positive correlation between PLR levels and SII (P<0.001). In addition, a nonlinear relationship between PLR and SII was tested using a smoothed curve fit after adjusting for potential confounders. Multiple segmented linear regression models showed a significant relationship between SII and PLR in both SII < 1,326.47 (β 0.14, 95% CI: 0.12, 0.16; P<0.0001) and >1,326.47 (β 0.02, 95% CI: −0.01, 0.05; P = 0.2461). Conclusions. In conclusion, this study showed a nonlinear relationship between SII and PLR in patients with uterine adenomyosis. An increase in serum PLR levels correlates with an increase in SII before SII levels reach an inflection point.